Synchrony between fish feeding guilds and habitat associations in a regulated Great Plains river - Rowley, Logan R. (My University, 2025)
The effects of river regulation on fish populations and their habitats are complex and further comprehension is needed for effective management and conservation. Specifically, we sought to understand if habitat variability alters the distribution of fish species and their diets in a Great Plains riverscape. Fish, aquatic macroinvertebrates, and habitat measurements were collected at seven sites in the regulated Kansas and Big Blue rivers. We used multivariate analysis of fish diets and fish habitat associations to identify feeding and habitat guilds and tested their dependencies using a fourth corner approach. We found that although there was a large degree of diet overlap for most assemblage members, species diets could generally be used to distinguish four feeding guilds: herbivore, omnivore, benthic invertivore, and pelagic/terrestrial invertivore. We also ascertained that species were distributed along a habitat gradient with mid-channel species like emerald shiners Notropis athernoides and carmine shiners N. percobromus on one end and a near shore assemblage of western mosquitofish Gambusia affinis, bluntnose minnows Pimephales notatus, and sand shiners N. stramineus on the other. The fourth corner analysis provided some support (p-value = 0.08) for the synchrony between the diets of species and their habitats, suggesting a mechanism by which river regulation and associated changes in habitat might influence fish populations through the food web. A more comprehensive understanding of how flow regulation impacts the distribution of habitats in the riverscape is necessary to better implement this knowledge into management and conservation of regulated rivers.
Keywords: Fish; Ecology; Diet; Regulated rivers; Kansas river; Habitat